Pemberdayaan Masyarakat melalui Pembagian dan Edukasi Pemanfaatan Tanaman Obat Keluarga (TOGA) sebagai Upaya Meningkatkan Kemandirian Kesehatan di Desa Loram Wetan Kabupaten Kudus - Rian Efendi; Himmatul Ulya (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The utilization of Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) as a local resource to support family health maintenance in Loram Wetan Village, Kudus Regency, still needs to be improved. Limited community knowledge regarding the benefits, cultivation, and maintenance of medicinal plants, as well as the suboptimal use of home gardens, provided the basis for implementing this community service activity. The activity aimed to increase the knowledge and awareness of members of the Main Family Welfare Empowerment (PKK) regarding the utilization of medicinal plants while providing access to plants that could be developed as a family living pharmacy. The activity was conducted using a participatory approach through observation and coordination with the Head of the PKK on August 4, 2026, followed by education and distribution of medicinal plants to members of the Main PKK on August 8, 2026. The activity took place in the Hall of the Loram Wetan Village Office and was attended by 26 members of the Main PKK. The results showed that the medicinal plant distribution and education program was successfully implemented as planned and provided participants with plants and basic knowledge regarding the utilization and maintenance of medicinal plants. The distributed plants can be cultivated in participants’ home environments as an initial step toward establishing a family living pharmacy. The expected impacts of this activity include increased community awareness of the utilization of local resources, optimization of home gardens, and the development of sustainable habits of planting and maintaining medicinal plants. The outputs of the activity included the implementation of education on the utilization of medicinal plants, the distribution of medicinal plants to members of the Main PKK, and the establishment of a foundation for developing family living pharmacies in Loram Wetan Village.